Molecular dynamics simulations of mechanical properties of swollen nitrile rubber composites by incorporating carbon nanotubes. Issue 8 (14th April 2020) - Yang, Bin; Wang, Shijie; Li, Yunlong; Liming, Tang; Enqiu, He; Song, Shuyuan
Abstract: Molecular models of pure and 10% and 20% swollen nitrile rubber matrices were developed. Different amounts of carbon nanotubes (CNTs) were incorporated into the swollen nitrile rubber matrices. The effects of the swelling behaviors and introduced CNTs on the mechanical properties of the nitrile rubber matrices were investigated using molecular dynamics simulations. The simulation results show that compared to the pure nitrile‐butadiene rubber (NBR) models, the elastic moduli and tensile strengths of the nitrile rubber matrices were reduced by ~31.72% and 20.10% (at a swelling ratio of 10%) and 68.28% and 36.82% (at a swelling ratio of 20%), respectively. Compared to those of the swollen NBR models without CNTs, after the introduction of one CNT, the elastic modulus and tensile strength improved by ~67.02% and 4.17% (at a swelling ratio of 10%) and 215.27% and 7.00% (at a swelling ratio of 20%), respectively. The mechanical properties of the nitrile rubber matrix improved when the content of CNTs increased. The radial distribution functions of the rubber materials, interfacial energies of the reinforced regions, and mean square displacements and diffusion coefficients of the solutions were analyzed. The introduced CNTs blocked the diffusion of the solute in the nitrile rubber matrix. This study elucidates the swelling behaviors of rubber materials from an atomic perspective and mechanical properties of carbon‐nanotube‐reinforced swollen rubber matrices.